Survey of Economic and Social Developments in the Arab Region 2014-2015 - United Nations Economic; Social Commission for Western Asia (United Nations, 2015)
In addition to conflicts and related security disruptions in the Arab region, a significant fall in oil prices and their uncertain prospects have become a predominant economic concern, with prices plunging by more than 50 per cent in the second half of 2014. Nevertheless, member countries of the Gulf Cooperation Council (GCC) have continued to lead growth in the Arab region. This edition of the Survey of Economic and Social Developments in the Arab Region looks at the continued expansion of the non-oil sector as it maintains GCC economic growth. Lower oil prices have not yet negatively affected the GCC economically, although confidence has dropped with weakening stock markets and real estate transactions. Furthermore, lower oil prices have benefited oil-importing Arab countries by easing their balance-of-payment and fiscal constraints. With conflict and violence in the region, one of the main channels for economic stabilization has been intraregional flows of capital and remittances from the GCC countries.